Competitive Analysis of Online Ecommerce Fashion Stores in Georgia : A Comparative Approach - Revazishvili, Mari (2025)
This thesis examines the competitive dynamics of Georgia’s rapidly developing online fashion e-commerce market through the application of competitive intelligence (CI) frameworks. By integrating PESTLE analysis, Porter’s Five Forces, digital analytics, and comparative case studies, the research provides a structured assessment of how local and international players compete within an evolving digital ecosystem shaped by rising smartphone adoption, improving payment systems, and shifting consumer expectations. The study maps the external environment influencing Georgian e-commerce, highlighting how economic conditions, regulatory developments, and social trends create both opportunities and constraints for market participants. It further analyses the competitive landscape, demonstrating how global platforms exert strong price and assortment pressure, while local retailers compete through service quality, localisation, and brand trust. A detailed comparative case study of DressUp.ge and ICRshop.ge reveals two distinct strategic models. DressUp.ge leverages digital visibility, social media engagement, and service innovation, while ICRshop.ge relies on premium brand partnerships and the strength of its offline retail network. Benchmarking data from Similarweb and SEMrush illuminate differences in traffic, keyword positioning, engagement patterns, and domain authority, offering measurable insights into their competitive standing. The findings identify strategic opportunities for both existing retailers and potential entrants, including mid-premium positioning, improved omnichannel integration, sustainability-oriented offerings, and mobile-first innovation.